Levodopa in Parkinson’s Disease: Current Status and Future Developments - Tambasco, Nicola (Curr Neuropharmacol, 2018)
BACKGROUND: Ever since the pioneering reports in the 60s, L-3,4-Dioxyphenylalanine (levodopa) has represented the gold standard for the treatment of Parkinson’s Disease (PD). However, long-term levodopa (LD) treatment is frequently associated with fluctuations in motor response with serious impact on patient quality of life. The pharmacokinetic and pharmacodynamic properties of LD are pivotal to such motor fluctuations: discontinuous drug delivery, short half-life, poor bioavailability, and narrow therapeutic window are all crucial for such fluctuations. During the last 60 years, several attempts have been made to improve LD treatment and avoid long-term complications. METHODS: Research and trials to improve the LD pharmacokinetic since 1960s are reviewed, summarizing the progressive improvements of LD treatment. RESULTS: Inhibitors of peripheral amino acid decarboxylase (AADC) have been introduced to achieve proper LD concentration in the central nervous system reducing systemic adverse events. Inhibitors of catechol-O-methyltransferase (COMT) increased LD half-life and bioavailability. Efforts are still being made to achieve a continuous dopaminergic stimulation, with the combination of oral LD with an AADC inhibitor and a COMT inhibitor, or the intra-duodenal water-based LD/ carbidopa gel. Further approaches to enhance LD efficacy are focused on new non-oral administration routes, including nasal, intra-duodenal, intrapulmonary (CVT-301) and subcutaneous (ND0612), as well as on novel ER formulations, including IPX066, which recently concluded phase III trial. CONCLUSION: New LD formulations, oral compounds as well as routes have been tested in the last years, with two main targets: achieve continuous dopaminergic stimulation and find an instant deliver route for LD.